Genetics in clinical epilepsy: Issues in genetic testing and counseling - Sheidley, Beth Rosen; Poduri, Annapurna (Journal of Pediatric Epilepsy, 2012)
In the last decade, major advances have been made in our understanding of the genetic basis of epilepsy. Genetic testing for over two dozen epilepsy-related genes is now clinically available, and healthcare providers who manage patients with epilepsy are faced with incorporating genetic information into their assessment and treatment plans. Although the clinical applications of genetic test results in the setting of epilepsy may be somewhat limited, an argument for the utility of testing can be made based upon the potential impact on treatment options, the ability to provide prognostic information, and the psychological, medical, and reproductive implications for patients and their family members. Clinicians who incorporate genetic testing into their evaluation of patients with epilepsy must be knowledgeable about epilepsy phenotypes and epilepsy genes, have expertise in eliciting a genetic family history that encompasses not only epilepsy but a broader range of relevant medical conditions, and possess a thorough understanding of genetic testing methods and outcomes. Given the complexity of genetic test results, it is crucial that informed consent to discuss the risks, benefits, and limitations of genetic testing take place with patients prior to testing. In addition, many patients may benefit from genetic counseling to discuss testing options or results, address family impact or reproductive issues, and obtain access to support resources.
Keywords: Epilepsy; genetics; genetic counseling; epilepsy genes